3.55 keV photon lines from axion to photon conversion in the Milky Way and M31 - Conlon, J; Day, F (Institute of Physics Publishing, 2014)
We further explore a scenario in which the recently observed 3.55 keV photon line arises from dark matter decay to an axion-like particle (ALP) of energy 3.55 keV, which then converts to a photon in astrophysical magnetic fields. This ALP scenario is well-motivated by the observed morphology of the 3.55 keV flux. For this scenario we study the expected flux from dark matter decay in the galactic halos of both the Milky Way and Andromeda (M31). The Milky Way magnetic field is asymmetric about the galactic centre, and so the resulting 3.55 keV flux morphology differs significantly from the case of direct dark matter decay to photons. However the Milky Way magnetic field is not large enough to generate an observable signal, even with ASTRO-H. In contrast, M31 has optimal conditions for a → γ conversion and the intrinsic signal from M31 becomes two orders of magnitude larger than for the Milky Way, comparable to that from clusters and consistent with observations.